2016
DOI: 10.1128/jvi.02642-15
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Perturbation-Associated Ca 2+ Signaling and Incoming Genome Sensing Are Required for the Host Response to Low-Level Enveloped Virus Particle Entry

Abstract: The type I interferon (IFN) response is an important aspect of innate antiviral defense, and the transcription factor IRF3 plays an important role in its induction. Membrane perturbation during fusion, a necessary step for enveloped virus particle entry, appears sufficient to induce transcription of a subset of IFN-stimulated genes (ISGs) in an IRF3-dependent, IFN-independent fashion. IRF3 is emerging as a central node in host cell stress responses, although it remains unclear how different forms of stress act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 56 publications
3
32
0
Order By: Relevance
“…For some viruses, viral entry has been shown to induce innate immune responses. For example, membrane fusion during entry of enveloped viruses, such as SeV, Semliki Forest virus (SFV), and human cytomegalovirus (HCMV), has been shown to induce IFN-␣/␤ or a subset of ISGs (54,55). Although we showed that NV and GII.3 VLPs do not induce an IFN response when they are added to the medium of 293FT cell culture (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…For some viruses, viral entry has been shown to induce innate immune responses. For example, membrane fusion during entry of enveloped viruses, such as SeV, Semliki Forest virus (SFV), and human cytomegalovirus (HCMV), has been shown to induce IFN-␣/␤ or a subset of ISGs (54,55). Although we showed that NV and GII.3 VLPs do not induce an IFN response when they are added to the medium of 293FT cell culture (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…How is fusion triggering orchestrated in multicomponent fusion machines? In another vein, recent work suggests that enveloped virus‐membrane fusion can spark signaling responses that trigger innate immune responses , and that cells can use interferon‐inducible transmembrane proteins to block virus–cell fusion . For their part, some viruses, notably HIV, have evolved means to counter attempts by cells to thwart virus–cell fusion .…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50][51][52] The direct recognition and killing of tumor cells are primarily mediated by natural killer (NK) cells of the innate system and tumor antigen-specific CD8+ cytotoxic T lymphocytes of the adaptive immune system (Figure 1). 13,40 In addition, OVs trigger an antiviral immune activation in tumor cells, even without productive replication, 53 that helps to activate antitumor immune stimulation. 54 PAMPs activate a cascade of signaling events that stimulate the inflammasome and activate different transcription factors, culminating in the release of pro-inflammatory cytokines and DAMPs.…”
Section: Ovt As Immunotherapymentioning
confidence: 99%